Synthesis of angiotensin-converting enzyme (ACE) inhibitors using dynamic kinetic resolution. Synthesis of the highly methylated tryptophan residue of hemiasterlin using glycidic ester ring opening reactions. Synthesis of benz(o)indenes. - Jaquith, James B. (University of Ottawa (Canada), 1999)
This thesis consists of four separate chapters. The first three chapters contain a common theme; the diastereoselective synthesis of medicinally relevant compounds using Dynamic Kinetic Resolution (DKR). Unfortunately, in chapter three DKR could not be applied to our desired target, and an alternate route was found. This chemistry allowed for the preparation of two novel classes of bis-indole compounds. Chapter four is unrelated to the first three chapters and describes the synthesis of two tricyclic chiral ligand precursors, using known ring annulation techniques. Chapter One. DKR was applied to the preparation of the core structures of several Angiotensin-converting Enzyme (ACE) inhibitors. High levels of diastereoselectivity were observed in the DKR of [ R]-pantolactone 2-iodo-4-phenylbutanoate with benyl and dibenzylamine, several chiral alpha-amino esters, and [S]-2-aminocaprolactam. The benzolactam core of benazepril was prepared by the DKR of [R]-pantolactone 2-iodo-4-(2-nitrophenyl)butanoate with benzylamine, and reductive cyclization of the resultant DKR product. Chapter Two. The treatment of alpha-halo [ R]-pantolactone esters with various diamines resulted in the formation of optically active 6 membered heterocycles, via DKR mediated displacement of the halide followed by transamidation. Alternately, this reaction yielded diastereomerically enriched bis-alpha-amino esters when the chain length between the amines was greater than 3 carbon atoms. Similarly, alpha-halo [R]-pantolactone acrylates provided 6 membered heterocyclic esters, via a 1,4-Michael addition of one amine to the acrylate, followed by DKR mediated halide displacement by the second amine. Moderate to high levels of diastereoselectivity were observed in these reactions. Chapter Three. beta,beta-Disubstituted and beta-monosubstituted glyoxylate esters reacted with substituted indoles and SnCl4, to provide highly substituted tryptol derivatives in 45 to 70% yield. Conversion of these trytols to the corresponding azides was facilitated by the Mitsunobu reaction, however, it proved difficult to reduce these azides to the corresponding tryptophan derivatives. Ringing opening reaction using ZnI2 as the Lewis acid provided access to alpha,alpha-bis(indolyl) esters. Modifications to this chemistry provided access to alpha,beta- bis(indolyl) esters. Chapter Four. 4,5-Benz-1-indene was prepared regioselectively, in 45--50% yield, after 5 steps, via a modified ring annulation/dehydration process. This new synthetic strategy dramatically increased the overall yield while simplifying the synthetic manipulations required for its preparation. A similar procedure was used in the preparation of a new ligand precursor 8,9,10,11-tetrahydro-4,5-benz(o)indene, in 22% overall yield, after 7 steps.
Keywords: Chemistry, Organic.